Mampukah Rasio Pembayaran Dividen Memperkuat Efek Return On Asset, Debt To Equity Ratio Dan Current Ratio Terhadap Price To Book Value? - Permana, Muh. Agung; Kadir, Muh. AKob; Kanto, Muklis (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The study aims to test the ability of the dividend payout ratio as a moderation in strengthening the effect of ROA, DER and CR on the price to book value of private banks listed on the Indonesian stock exchange. This research is quantitative and uses secondary data. The population of this study is 13 private banks, sampling using purposive samplings with the number of samples meeting the criteria of as many as 13 companies that publish full financial statements from the year 2020-2022 so that the total sample used amounts to 39 out of data analysis. Panel data regression analysis is used with Eviews 13. The results of this study show that the profitability variable (ROA) has a positive and non-significant effect on the value of the company (PBV), the leverage (DER) has negative and insignificant effects on the company's value, and the liquidity (CR) have a negative and significant impact on the firm value. In other tests, evidence was obtained that the dividend payout ratio (DPR) cannot strengthen the profitability effect on the firm's value, dividend payout ratio proved to be able to reinforce the effect of leverage on firm value, and the dividend payout ratio cannot reinforce liquidity effect on firm value